Are there signals of a housing bubble?: an empirical analysis of the portuguese case - Tavares, Márcia Filipa Martins (2020)
Is there a housing bubble emerging in the Portuguese real estate market? Since similar questions have been raised among the popular press, and among economists and policymakers, the housing market in Portugal has becoming an extremely interesting topic to be investigated within the OECD area. The foremost purpose of this dissertation is to evaluate whether there are bubble tendencies in the Portuguese housing market, or if the (apparently) continuous house price growth can be explained by economic fundamental factors. The first point we would like to stress is that, for the period where there is consistent and comparable data related to house prices in the OECD countries (since 1988), Portugal displays the smallest rate of growth of real house prices. Secondly, the multiple linear regression model suggests an unexpected finding: the hypothesis of an emerging housing bubble in the Portuguese market can be easily rejected. As a matter of fact, and regardless of people's beliefs, there is no sound of an economic evidence of a boom-bust in real house prices. Portugal is not in an alarming situation and so we can throw away the idea that the country is facing a speculative momentum. Surprisingly, the increase in housing prices that have been distressing the whole Portuguese society seems to be nothing else than a typical price adjustment, which results from the large previous downward fall that house prices suffered in the aftermath of the recent sovereign debt crisis, which so dramatically affected the whole Portuguese economy.